A Review on Hand-operated Product Parameters Influencing Hand Grip of Senior Citizen - Halim, Isa; Radin Zaid Radin Umar,; Adi Saptari,; Padmanathan, Vinothini (International Journal of Integrated Engineering, 2020)
The number of senior citizens around the world is increased and consequently ergonomically designed hand-operated products are necessities and play vital role in their daily life. However, designing hand-operated products for senior citizen users pose distinct challenges because the design parameters are different from the young adults requirements. The aim of this paper is to present a comprehensive overview on design parameters of hand-operated products that influencing hand grip of senior citizens. The authors searched the information of design parameters from journal articles, conference proceedings, doctoral dissertations and guidelines from online databases such as Google Scholar, ScienceDirect and Pubmed. Six main design parameters of hand-operated products were identified to influence hand grip of senior citizens. The design parameters can be categorized as:    1) weight; 2) shape, grip span, size; 3) materials, contact surface, friction coefficient; 4)  force, torque and spring stiffness; 5) diameter, length and orientation of handle; 6) clearance or allowance. These parameters met the principles of ergonomic designs that allow senior citizens to operate hand-operated products with neutral wrist posture, less muscle effort and ease of use.